A holonic control approach for distributed manufacturing - Leitão, Paulo (2010)
Nowadays, manufacturing systems are complex and often chaotic environments, being collated with customer satisfaction, products shorter life cycle and new e-business trends, becoming the design of manufacturing control applications a complex and hard task. As the traditional control approaches present serious problems to handle simultaneously the distribution of functions, global production optimisation, reaction to disturbances and reconfiguration, it is necessary to introduce new concepts and technologies that support the new intelligent manufacturing control systems. The paper introduces an innovative holonic manufacturing control architecture to face some of these unsolved problems by supporting an increase of flexibility and an agile reaction to disturbances without compromising the global production optimisation, being regulated by a coordination mechanism that allow fast reaction and adaptation to disturbances.